Avaliação biológica e físico-química da carne de avestruz (Struthio camelus) e seu efeito nos paramêtros bioquímicos em ratos - Hautrive, Tiffany Prokopp (2008)
The ostrich meat is being introduced in the market for meat as a healthy alternative when compared with most other meat, because it has low content of total lipids, saturated fatty acids and calories. Despite these benefits reported in the scientific literature on the ostrich meat, there are few jobs in relation to protein quality and effect of the consumption of meat on the metabolism of humans and animals. This study aims to assess the biological and physical chemistry of ostrich meat, its effect on biochemical parameters in rats and compared with most other meat consumed. We performed analysis of proximate composition, fatty acid profile, cholesterol and minerals of ostrich meat, beef, pork and chicken. To test the biological, experimental diets were prepared with casein (control) and diets in which casein was replaced by ostrich meat, beef, chicken and pork. The proximate composition of meat, for moisture, protein and ash, was very similar, but the meat of ostriches showed a lower percentage of lipid (0.58%). Moreover, had a good relationship of polyunsaturated fatty acids / saturated (0.99) n6/n3 ratio (8.32) and greater amount of iron (4.17 mg/100g). By the assay it was found that as well as beef, pork and chicken, beef and ostrich has an excellent quality protein and showed positive results in the biochemical parameters of rats fed with this meat, especially in relation to serum cholesterol of animals that showed a lower concentration.